ON THE QUESTION OF EXPECTANT MANAGEMENT OF LABOR IN FULL-TERM PREGNANCY COMPLICATED BY PREMATURE RELATION OF AMBIENT FLUID - Kayumova G.M. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
RELEVANCE OF THE PROBLEM Premature is the rupture of amniotic fluid when the membranes rupture before the onset of labor, regardless of the stage of pregnancy. Premature rupture of membranes occurs in 2.7–17% of cases [1]. Antenatal rupture of membranes is a complex obstetric problem associated with a high risk of perinatal and maternal morbidity. As a result of premature rupture of the membranes, small parts of the fetus, especially the umbilical cord, may fall out. Oligohydramnios or anhydria that occurs after premature rupture of the membranes create conditions for threatening unilateral compression of the umbilical cord and placenta by individual parts of the fetus or the entire fetus, which often leads to asphyxia [2]. However, the most common unfavorable prognosis for mother and child is due to the development of septic complications [3]. The frequency of infection after premature rupture of membranes is directly dependent on the duration of the anhydrous period (the time between rupture of membranes and birth of the fetus) [4]. Despite significant advances in obstetric science, the problem of rational management of pregnancy and childbirth complicated by premature rupture of amniotic fluid remains insufficiently resolved. There is no consensus regarding the tactics of managing urgent labor complicated by premature rupture of membranes. Issues related to induction of labor depending on the duration of the anhydrous period and the prevention of infectious complications are controversial. Some authors recommend starting labor induction immediately after a diagnosis of premature rupture of amniotic fluid is made. Others believe that in the absence of symptoms indicating the presence of infection, vaginal delivery is contraindicated and one can wait for the spontaneous onset of labor [1].